2008
DOI: 10.1088/1742-6596/100/8/082039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various deposition conditions on the electrical properties of LAO/STO hetero interfaces

Abstract: We have examined the effects of partial oxygen pressure and laser energy density on the electrical transport properties of thin LAO films grown on (100) TiO 2-terminated SrTiO 3 substrates. Films were grown by pulsed laser deposition monitored by in-situ reflection highenergy electron diffraction (RHEED). Layer-by-layer growth, as indicated by clear RHEED oscillations, can be obtained in a wide range of oxygen partial pressures from 10-6 to 5x10-2 mbar. Transmission electron microscopy (TEM) analysis shows tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
58
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(70 citation statements)
references
References 7 publications
8
58
3
Order By: Relevance
“…Another important feature of the LAO/STO interface is the dependence of its electrical properties on oxygen pressure during deposition of the LAO film. An increase of the oxygen pressure results in decreased conductivity and even insulating behavior [7,8]. These observations are difficult to explain altogether assuming electronic or ionic models separately.…”
mentioning
confidence: 99%
“…Another important feature of the LAO/STO interface is the dependence of its electrical properties on oxygen pressure during deposition of the LAO film. An increase of the oxygen pressure results in decreased conductivity and even insulating behavior [7,8]. These observations are difficult to explain altogether assuming electronic or ionic models separately.…”
mentioning
confidence: 99%
“…As it was previously reported, STO is a wide band gap semiconductor with a band gap of about 3.2 eV and is n‐doped by the pristine oxygen vacancies. [ 21 ] The oxygen vacancy in STO introduces defect levels at 0.28–0.7 eV under the conduction band, which can be easily photoionized. [ 10 ] Moreover, previous studies showed that the STO surface (within a few nm) accumulates oxygen vacancies that induce shallow defect levels within the band gap.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, a polar discontinuity arises at the interface. Depending on the substrate termination, this system can be either insulating or conductive, where the charge carrier density and mobility depends on the LaAlO 3 thickness and the growth conditions [15][16][17][18][19]. Although a large number of complementary method have been applied to investigate the system, the reason for its unusual behavior is still under debate.…”
Section: Surface and Interface Propertiesmentioning
confidence: 99%